Apolipoprotein E gene polymorphisms as risk factors for carotid atherosclerosis - Zurnić, Irena; Djurić, Tamara; Končar, Igor; Stanković, Aleksandra; Dinčić, Dragan; Živković, Maja (Vojnosanitetski pregled, 2014)
Background/Aim. Atherosclerosis is still the leading cause of death in Western world. Development of atherosclerotic plaque involves accumulation of inflammatory cells, lipids, smooth muscle cells and extracellular matrix proteins in the intima of the vascular wall. Apolipoprotein E participates in the transport of exogenous cholesterol, endogenously synthesized lipids and triglycerides in the organism. Apolipoprotein E gene has been identified as one of the candidate genes for atherosclerosis. Previous studies in different populations have clearly implicated apolipoprotein E genetic variation (ε polymorphisms) as a major modulator of low density lipoprotein cholesterol levels. Data considering apolipoprotein E polymorphisms in relation to carotid atherosclerosis gave results that are not in full compliance. The aim of present study was to investigate the apolipoprotein E polymorphisms in association with carotid plaque presence, apolipoprotein E and lipid serum levels in patients with carotid atherosclerosis from Serbia. Methods. The study group enrolled 495 participants: 285 controls and 210 consecutive patients with carotid atherosclerosis who underwent carotid endarterectomy. Genotyping of apolipoprotein E polymorphisms were done using polymerase chain reaction and restriction fragment length polymorphism methods. Results. Patients had significantly decreased frequency of the ε2 allele compared to controls. Patients who carry at least one ε2 allele had a significantly higher level of serum apolipoprotein E and significantly lower low density lipoprotein cholesterol levels compared to those who do not carry this allele. Conclusion. Our results suggest protective effect of apolipoprotein E ε2 allele on susceptibility for carotid plaque presence as well as low density lipoprotein cholesterol lowering effect in Serbian patients with carotid atherosclerosis. Further research of multiple gene and environmental factors that contribute to the appearance and the progression of atherosclerosis should be continued with respect to different populations.